Posisi Hukum Anak Astra Dalam Adat Bali: Relevansi Kedaulatan Hukum Adat Di Tengah Sistem Hukum Nasional - Widia Asih, Dewa Ayu Putu; S, Sepriyadi Adhan; Wiranata, I Gede AB; Kasmawati, Kasmawati; Sumarja, FX; Zazili, Ahmad (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
The legal position of astra children (children out of wedlock) in the structure of Balinese customary law, especially in inheritance rights and social participation in customary communities, often faces discrimination because their position is not fully recognized in the paternal lineage, which has implications for inheritance rights, participation in traditional ceremonies, and other social rights. Through a juridical-normative approach, this article aims to analyze the legal position of astra children (children out of wedlock) in the structure of Balinese customary law, inheritance rights, and social participation in customary communities. It also identifies tensions and conflicts between customary law and national law. Although the Constitutional Court Decision Number 46/PUU-VIII/2010 has given legal recognition to extra-marital children, its implementation in the customary realm still faces social and cultural resistance. The tension between the principle of customary law sovereignty and the supremacy of national law is the main highlight. This research shows that the position of astra children in Balinese customary law is influenced by the legitimacy of the biological father and the role of the extended family which has a direct impact on their civil and customary rights. Thus, there is a need for equal legal dialogue between the state and indigenous communities to find common ground that guarantees the protection of astra children's rights without eliminating the identity of customary law that is still alive in the community.